The manager's pocket guide to spiritual leadership transforming dysfunctional organizations into healthy communities - Bellingham, Richard; Meek, Julie; Safari eBooks (Amherst, MA : HRD Press, 2001)
"The quality of life in organizations is deteriorating. People don't have a sense that their work has meaning. Cynicism reigns. People don't want to live and work in this way and organizations don't function optimally when they do. Leadership will need to attend to our source of enthusiasm and inspiration-our soul. A new style of leadership is required, one that makes collaboration, empowerment, and innovation possible. This guide provides methods for engaging in the transformational process. It contains practical ways to measure healthy communities, healthy people, and quality of work life, and is also grounded in reality. The authors have spent more than 25 years, in hundreds of organizations, seeking out and developing spiritual leaders."--Resource description page.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Leadership; Corporate culture; Organizational change; Personnel management; Electronic books